Preliminary studies on enzymatic deinking - Pala, Helena (1998)
Results on enzymatic deinking of paper pulps are shown. The process includes paper pulping, with an enzymatic cocktail, followed by flotation and dewatering. Three different wastepaper samples were used and tested. The deinking of the pulp was monitored by image analysis. Physical, mechanical and optical properties of pulp and paper were also determined. The obtained data revealed the effectiveness of the assayed enzyme preparation. However, enzyme use needs further optimisation as paper strenght properties suffered important alteration.